Study on fatigue test specimen designs for additive manufacturing applications - Koo, Gary Jun Jie (Nanyang Technological University, 2024)
Additive Manufacturing parts are rising to use across various industries and hence the study of fatigue behavior is crucial to make sure it is safe for application usage. Both Inconel 718 and Ti-6Al-4V have good mechanical properties which is why they are commonly been used in the industry for engineering applications. In this project, specimens made with the Selective Laser Melting additive manufacturing technology for Inconel 718 and Ti-6Al-4V are evaluated for fatigue properties. A total of 12 fatigue specimens are printed and tested to gather the fatigue data required to plot the S-N curves. Fractography was also conducted after the fatigue test to look into the facture surfaces for fatigue failure. The results shows that Ti-6Al-4V fatigue life is lower than Inconel 718 due to the porosity that are created during the printing process. Future work can be done to help improve the quality of the materials printed so to achieve better results.